Pattern of Mobile Phone Use among Students of An Institution - Kriti Thapa; Rita Pokharel; Rambha Sigdel; Surya Prasad Rimal (Journal of Nepal Medical Association, 2018)
Introduction: The charm of mobile phone is more among young generation and the increasing use can lead to various harmful effects and may result in dependence. The objective of the study is to evaluate the pattern of mobile phone use among medical students.